Visual Inspection With Acetic Acid (Via) Positive Results And Passive Smoker In Puskesmas Wonoayu Sidoarjo - Ursia, Catharina C; Warsanto, JA; Isbandiati, Endang (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Introduction: Cervical cancer is a malignancy in women with the number one mortality and number two morbidity in the world. As many as 77% cases are found in developing countries, including Indonesia. Although deadly, screening programs can reduce the morbidity and mortality of this malignancy. Visual Inspection with Acetic Acid (VIA) is a cervical premalignancy screening method used in primary health care in Indonesia. Smoking is one of risk factor associated with cervical cancer and data from GATS, Infodatin 2015 & Riskedas 2013 states that the number of passive smokers in Indonesia is high. Aim: The objective of this research is to look for the correlation between history of passive smoker and positive VIA Methods: This research is a retrospective cross sectional analytic study. The data used in this study is the medical records of VIA screening visitors in 2016. The data were extracted on the research questionnaire. Data processing is done by using SPSS Statistics 23 For Windows computer software. The test is Chi Square correlation test and calculation of Prevalence Ratio (PR). Result: 55 women (24.7%) had a history of passive smoking (daily cigarette smoke exposure), and 168 women (75.3%) had no daily cigarette smoke. 21 women (9.4%) received positive results, and 202 women (90.6%) received negative IVA. In the Pearson Chi-Square section, the Asymptotic Significance (2-sided) yielded results at 0.042 (p